New Approaches to CSR, Sustainability and Accountability, Volume II - Çalıyurt, Kıymet Tunca (Accounting, Finance, Sustainability, Governance & Fraud: Theory and Application, 2021)
XXX, 208 p. 40 illus., 19 illus. in color.